MAPPING THE SCIENTIFIC LANDSCAPE OF WORK-LIFE BALANCE AND EMPLOYEE WELL-BEING: - Riyadi, Akhmad; Hendar, Hendar (Politeknik Bisnis Indonesia, 2025)
This study aims to analyze trends and patterns in research related to work-life balance (WLB) and employee well-being using a combined approach of Systematic Literature Review and bibliometric analysis. A dataset consisting of 151 articles published between 2013 and 2025 from the Scopus database was used. The findings highlight the growing scientific interest in work-life balance (WLB) and its impact on well-being in a post-pandemic context, especially under hybrid work models. VOSviewer is used to visualize the occurrence of keywords and research groups. The review identifies dominant themes, prolific authors, and geographic contributions, which provide a roadmap for future research.